Structural and mechanical properties of (Co/Mg) co-doped nano ZnO - Asikuzun, E.; Donmez, A.; Arda, L.; Cakiroglu, O.; Ozturk, O.; Akcan, D.; Tosun, M.; Ataoglu, S.; Terzioglu, C. (Elsevier BV, 2015)
Abstract The (Co/Mg) co-doped ZnO systems (ZnMgCoO) were synthesized as polycrystalline nanoparticles using the sol–gel technique. The effects of Co/Mg co-addition to the structural and mechanical properties of ZnO nanoparticles were investigated. Microstructural properties, such as phases, crystal structures and grain sizes are characterized by using X-Ray Diffraction (XRD) analysis and Scanning Electron Microscope (SEM). The microhardness values of the samples were evaluated by the Vickers tester. In the samples of the Co>Mg ratio, Indentation Size Effect (ISE) behaviors were observed. On the other hand, in the samples of the Mg>Co ratio, Reverse Indentation Size Effect (RISE) was observed. These were analyzed in detail utilizing the models for materials hardness analysis found in literature.
Keywords: Microhardness; Co/Mg; Sol gel; ZnO; Mechanical Properties; 2. Zero hunger; 3. Good health